2016
DOI: 10.1175/jtech-d-15-0176.1
|View full text |Cite
|
Sign up to set email alerts
|

Taking into Account Atmospheric Uncertainty Improves Sequential Assimilation of SMOS Sea Ice Thickness Data in an Ice–Ocean Model

Abstract: The sensitivity of assimilating sea ice thickness data to uncertainty in atmospheric forcing fields is examined using ensemble-based data assimilation experiments with the Massachusetts Institute of Technology General Circulation Model (MITgcm) in the Arctic Ocean during November 2011-January 2012 and the Met Office (UKMO) ensemble atmospheric forecasts. The assimilation system is based on a local singular evolutive interpolated Kalman (LSEIK) filter. It combines sea ice thickness data derived from the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…However, further work needs to be done to better understand the uncertainty of the assimilated SIT from the SMOS-Ice. Recently, Yang et al (2016) tested the sensitivity of assimilating the SMOS-Ice data with the LSEIK during the winter of 2011-2012, and they found that perturbations of the atmospheric forcing is important for improving the performance of assimilation, in agreement with Lisaeter et al (2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, further work needs to be done to better understand the uncertainty of the assimilated SIT from the SMOS-Ice. Recently, Yang et al (2016) tested the sensitivity of assimilating the SMOS-Ice data with the LSEIK during the winter of 2011-2012, and they found that perturbations of the atmospheric forcing is important for improving the performance of assimilation, in agreement with Lisaeter et al (2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The spatial resolution of the sea ice concentration data is 12.5 km × 12.5 km in a polar stereographic projection. Following Yang, Losch, Losa, Jung, Nerger, and Lavergne () and Yang, Losch, Losa, Jung, and Nerger (), a uniform constant value of 0.25 fractional sea ice area is assumed as observational uncertainties accounting for measurement and representation errors (Janjić et al, ) in the study.…”
Section: The Model Sea Ice Thickness Estimatesmentioning
confidence: 99%
“…For example, Lisæter et al () showed in idealized experiments with synthetic CryoSat data that sea ice and ocean state variables improve with sea ice thickness data assimilation. A series of studies also showed that the assimilation of SMOS ice thickness significantly improves the first‐year ice estimates (Yang et al, ; Yang, Losch, Losa, Jung, & Nerger, ; Xie et al, ). Assimilating CryoSat‐2 ice thickness data in addition to SMOS ice thickness into an ice‐ocean model in the cold season leads to a reliable pan‐Arctic sea ice thickness estimate that is consistent with in situ observations (Mu et al, ) .…”
Section: Introductionmentioning
confidence: 99%
“…() with the aim to improve 24 h‐forecasts of perennial sea ice thickness. To achieve this, the weekly averaged CryoSat‐2 ice thickness is assimilated into our forecasting system in addition to the Special Sensor Microwave Imager Sounder (SSMIS) sea ice concentration and SMOS sea ice thickness data (Yang et al., ). To account for atmospheric uncertainties, we follow Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…To account for atmospheric uncertainties, we follow Yang et al . (, ) and use the same ensemble atmospheric forcing from The Observing System Research and Predictability Experiment (THORPEX) Interactive Grand Global Ensemble (TIGGE) dataset (Park et al., ; Bougeault et al., ). The same autumn–winter seasonal transition period from 1 November 2011 to 30 January 2012 is chosen to simplify comparisons with Yang et al .…”
Section: Introductionmentioning
confidence: 99%